WEB-BASED OFFICE EQUIPMENT AND INVENTORY PROCUREMENT INFORMATION SYSTEM AT BANK MANDIRI, CENTRAL JAKARTA - Hanif Rahman Nasution; Susafa'ati Susafa'ati (International Journal Labs, 2022)
The manual procurement system for office stationery and inventory that has been felt so far has many shortcomings and is less effective and more time consuming, so it is necessary to develop effective and efficient goods management activities by building a procurement management information system through a web-based application, the use of which can be automatically and more familiar or very easy for the user. So the purpose of this system is to make it easier for Bank Mandiri staff to systematically monitor the procurement of equipment and investments. Interview is a process of communication or interaction to collect as much information as possible by means of question and answer. The Information System for the Procurement of Office Stationery (ATK) and Inventory has a system that automates the internet network so that it is safer and creates efficiency. Controlled the stock of incoming and outgoing goods. Facilitate monitoring of procurement and inventory data for Office Stationery (ATK) and inventory for decision making in management.